2014
DOI: 10.1177/0310057x1404200115
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex Hypersensitivity—A Case of Anaphylaxis

Abstract: We describe a case of a patient undergoing open abdominal aneurysm surgery who developed a severe, lifethreatening allergic reaction immediately after administration of sugammadex. The manifestation was purely a cardiovascular collapse. The mainstay of treatment was administration of high-dose adrenaline and fluid resuscitation. The diagnosis of anaphylaxis was supported by a positive serum mast cell tryptase (93 μg/l) at one hour post-event. Sugammadex was confirmed as the cause of the anaphylaxis by a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Four were in Japanese [14][15][16][17]; three were not primary investigations [18][19][20]; in the six from the MHRA, sufficient detail of the hypersensitivity reaction could not be disclosed owing to concerns over patient confidentiality; and one included a probable alternative explanation for the reaction [21]. We identified a total of 11 studies to be included in the qualitative analysis, including: two case series of three patients each [22,23]; six case reports [24][25][26][27][28][29]; an abstract [30]; and two clinical trials [7,31]. Table 1 summarises all the included patients.…”
Section: Methodsmentioning
confidence: 99%
“…Four were in Japanese [14][15][16][17]; three were not primary investigations [18][19][20]; in the six from the MHRA, sufficient detail of the hypersensitivity reaction could not be disclosed owing to concerns over patient confidentiality; and one included a probable alternative explanation for the reaction [21]. We identified a total of 11 studies to be included in the qualitative analysis, including: two case series of three patients each [22,23]; six case reports [24][25][26][27][28][29]; an abstract [30]; and two clinical trials [7,31]. Table 1 summarises all the included patients.…”
Section: Methodsmentioning
confidence: 99%
“…Most frequently reported side effects of SUG administration are pain, nausea, coughing, headache or vomiting 2,10, being the hypersensitivity reactions, ranging from erythema to anaphylactic shock, are the most alarming among them 27,28,29. Furthermore, allergy to NMB has been considered the first cause of perioperative anaphylaxis 30,31.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports described sugammadex‐induced anaphylactic reactions in adults . A previous study reported that incidence proportion of sugammadex‐induced anaphylactic reactions was estimated to be 0.003% .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Some reports described sugammadex-induced anaphylactic reactions in adults. [4][5][6][7][8][9][10] A previous study reported that incidence Accepted: 24 April 2018 DOI: 10.1111/pan.13401 proportion of sugammadex-induced anaphylactic reactions was estimated to be 0.003%. 7 However, the data were obtained from anesthesiologists on a voluntary basis, and may have been underreported.…”
Section: Introductionmentioning
confidence: 99%